Effect of solution treatment on the microstructure of dissimilar welding joints of Ta-10W and GH3128 - Fu Tao; Dong Li; Shudang Jia; Linhao Fan; Jieshi Chen (Materials Research Express, 2021)
Electron beam welding (EBW) process is employed to weld Ta-10W and GH3128 plates of 2 mm thick, which is very beneficial to the development of aerospace engine combustor. The microstructure of the as-welded (AW) and solution-treated (ST) samples are characterized. The phase transformation program of the fusion zone (FZ) of GH3128 and Ta-10W joints is ${\rm{L}}→ {\rm{L}}+{{\rm{M}}}_{6}{\rm{C}}→ {\rm{L}}+γ $ + ${{\rm{M}}}_{6}{\rm{C}}\,→ {\rm{L}}\,+$ $γ +{{\rm{M}}}_{6}{\rm{C}}+{{\rm{M}}}_{23}{{\rm{C}}}_{6}→ γ +{{\rm{M}}}_{6}{\rm{C}}$ + ${{\rm{M}}}_{23}{{\rm{C}}}_{6}→ γ +{{\rm{M}}}_{23}{{\rm{C}}}_{6}+{\rm{P}}.$ Whether in the AW or ST state, the reaction layers formed by hard intermediate phases are found between the FZ and Ta-10W. Comparing the two states, voids zone is formed at the interface of the reaction layer near the FZ in the ST state. Additionally, it is also found that the growth of the reaction layer was promoted at the solution temperature. It is certain that the solution treatment keeps many positive significances. First of all, the banded P phase worsening the properties of materials has not been formed. Secondly, the performance of the FZ is strengthened by the dispersed granular M _6 C. Thirdly, the distribution of coincident-site lattice (CSL) grain boundaries (GBs) in the FZ is more uniform than that in the AW state.